First demonstration of rapid shutdown using neon shattered pellet injection for thermal quench mitigation on DIII-D. (2nd March 2016) - Commaux, N.; Shiraki, D.; Baylor, L.R.; Hollmann, E.M.; Eidietis, N.W.; Lasnier, C.J.; Moyer, R.A.; Jernigan, T.C.; Meitner, S.J.; Combs, S.K.; Foust, C.R.
Abstract: Shattered pellet injection (SPI) is one of the prime candidates for the ITER disruption mitigation system because of its deeper penetration and larger particle flux than massive gas injection (MGI) (Taylor et al 1999 Phys. Plasmas 6 1872) using deuterium (Commaux et al 2010 Nucl. Fusion 50 112001, Combs et al 2010 IEEE Trans. Plasma Sci .38 400, Baylor et al 2009 Nucl. Fusion 49 085013). The ITER disruption mitigation system will likely use mostly high Z species such as neon because of more effective thermal mitigation and pumping constraints on the maximum amount of deuterium or helium that could be injected. An upgrade of the SPI on DIII-D enables ITER relevant injection characteristics in terms of quantities and gas species. This upgraded SPI system was used on DIII-D for the first time in 2014 for a direct comparison with MGI using identical quantities of neon. This comparison enabled the measurements of density perturbations during the thermal quench (TQ) and radiated power and heat loads to the divertor. It showed that SPI using similar quantities of neon provided a faster and stronger density perturbation and neon assimilation, which resulted in a lower conducted energy to the divertor and a faster TQ onset. Radiated power data analysis shows that this was probably due to the much deeper penetration of the neon in the plasma inducing a higher core radiation than in the MGI case. This experiment shows also that the MHD activity during an SPI shutdown (especially during the TQ) is quite different compared to MGI. This favorable TQ energy dissipation was obtained while keeping the current quench (CQ) duration within acceptable limits when scaled to ITER.